(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
As in many parts of the world, bilingualism is a common speech phenonmenon in Southwest Nigeria as many who have had exposure to western education are exposed to both Yoruba and English at about the same time and in the same environment. While Yoruba is the Mother Tongue, the English language is both the nations official as well as the second language and, by extention, the language common to many in this part of the countrys geopolitical zone. As the official language of education, the English language now faces serious challenges as it competes, in so many domains, with Yoruba, the language of the immediate environment, thus impinging negatively on the effectiveness of the use of the English language. The study is both a survey and descriptive using a simple questionnaire for the survey. The findings show a shift from the indigenous language to English,but the preference for English does not translate to mastery of the language. Results from public examinations indicate that the contact between the two languages affects the effective use of the English, which is the nations official language in schools. The study recommends, for the purpose of language planning, a tripartite lingustic model, with multilingualism at the base, for cultural matters, interpersonal communication in local trade and phatic communion; regional/geopolitical zone bilingualism in the middle of the pyramid, with the whole model peaking and coalescing at national monolingualism in a pyramidal form, with English retaining its prsent position at the peak of the pyramid.